America'S Shadow : An Anatomy of Empire - Spanos, William V. (Book collections on Project MUSE., 2000)
A study of imperialism that stretches from ancient Rome to the post-Cold War world and focuses on the Vietnam War, this provocative work boldly revises our assumptions about the genealogy of the West.